Formulation, Characterization and Evaluation of Metronidazole Gel for Local Treatment of Periodontitis - SHIVA KUMAR YELLANKI; JEET SINGH; FV MANVI (International Journal of Pharma and Bio Sciences, 2010)
In peridontial disease loss of tooth occures due to weakining of the supporting structure (pocket) of teeth, to prevent this site specific injectable drug delivery systems are required. In the present study six batches of metronidazole gels were prepared using natural biodegradable polymers Chitosan, guar gum and Locust bean gum in variable concentrations. The formulated gels were characterized for surface pH, viscosity, syringeability, bioadhesion strength, in vitro drug release studies and antimicrobial susceptibility test. The results revealed that the surface pH was within the range of neutral pH. The bioadhesion strength was maximum for F3 formulation (3% Chitosan); viscosity values were ranging from 1453.33 ± 5.77 to 1995.00 ± 0.01 dyne/cm2. Best formulation in terms of cumulative percent drug release along with bioadhesion was formulation F3 with 78.23 % drug release for 7 days and fulfilled many requirements of once a week delivery system, easy to fabricate, cost effective, patient compliance is also very high. Zone of inhibition was also satisfactory for all the formulations.